Implementasi Nilai-Nilai Adab Murid kepada Guru dalam Q.S. Al-Hujurat Ayat 1–5: Kajian Tafsir Maudhu'i dan Living Qur'an - Selfi Anna Harahap; Nawir Yuslem (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the values of students' etiquette (adab) toward teachers in Q.S. Al-Hujurat verses 1–5 using the thematic interpretation (tafsir maudhu'i) approach and investigates their implementation in educational practices at RA Al-Mukhlisin. A qualitative design was employed by integrating thematic Qur'anic interpretation and the Living Qur'an approach through library and field research. Data were collected through observation, in-depth interviews, and documentation, and analyzed descriptively with source and method triangulation to ensure credibility. The findings reveal that Q.S. Al-Hujurat verses 1–5 emphasize essential values of adab, including honoring teachers, refraining from preceding them in words or actions, maintaining respectful communication, lowering one's voice, obeying teachers' guidance, and preserving their dignity as a manifestation of respect for knowledge. These values are implemented through daily school practices, such as greeting teachers, kissing their hands, speaking politely, listening attentively during lessons, and complying with school regulations. The successful implementation is supported by teachers' exemplary conduct, parental involvement, and a religious school environment, while differences in family upbringing and external social influences remain significant challenges. This study contributes to strengthening Qur'an-based character education by integrating thematic exegesis and the Living Qur'an approach in early childhood Islamic education.